2020
DOI: 10.1002/alz.12241
|View full text |Cite
|
Sign up to set email alerts
|

Utility of MRI in the identification of hippocampal sclerosis of aging

Abstract: Introduction Hippocampal sclerosis of aging (HS) is a common pathology often misdiagnosed as Alzheimer's disease. We tested the hypothesis that participants with HS would have a magnetic resonance imaging (MRI)‐detectable hippocampal pattern of atrophy distinct from participants without HS, both with and without Alzheimer's disease neuropathology (ADNP). Methods Query of the National Alzheimer's Coordinating Center database identified 198 participants with MRI and autopsy. Hippocampal subfields were segmented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…This trend suggests larger sample sizes could reveal pairwise volume differences among HS stages and enable its in vivo classification. In agreement with histological findings, volume effects were not restricted to CA1 and subiculum, also in line with previously reported lower CA3 and CA4 volumes in HS 49 .…”
Section: Discussionsupporting
confidence: 92%
“…This trend suggests larger sample sizes could reveal pairwise volume differences among HS stages and enable its in vivo classification. In agreement with histological findings, volume effects were not restricted to CA1 and subiculum, also in line with previously reported lower CA3 and CA4 volumes in HS 49 .…”
Section: Discussionsupporting
confidence: 92%
“…Our results of associations between medial temporal lobe structures and hippocampal sclerosis of aging are also of interest. Many previous studies have noted that HS is associated with hippocampal atrophy 31-33 and one study has even noted associations outside the medial temporal lobe 34 . Also, other studies have found TDP-43, the proteinopathy signature of HS, to be associated with hippocampal 29 and additional brain atrophy 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is an increasing awareness that certain age-related neuropathologies such as TAR DNAbinding protein (TDP-43) and hippocampal sclerosis of aging (HS) are of greater importance in advanced age as they are much more common and strongly related to dementia in the oldest-old. Some in vivo neuroimaging studies in younger cohorts have begun to identify atrophy patterns on MRI related to TDP-43 [67][68][69] and HS [70,71]. However, given the importance and prevalence of TDP-43 and HS, more in vivo neuroimaging research focused specifically on the oldest-old and followed by pathological assessment is needed to try to identify biomarkers for these pathologies that cannot be identified during life.…”
Section: Summary and Future Directionsmentioning
confidence: 99%